Effectiveness of Dance Learning Model Based on Creative Workshops and Freedom to Learn to Develop Students' Cultural Literacy - Anggraini, Dwi; Tarmizi, Pebrian; Agusti, Ersa; Pertiwi, Ella Cahaya (Program Studi PGMI, 2025)
This research is motivated by the suboptimal cultural literacy of students in dance learning, so it is necessary to develop a dance learning model based on creative workshops and the principles of Freedom to Learn as an effort to overcome this problem and improve students' cultural literacy. This type of research uses quantitative research with a quasi-experimental method. The research design used is the Matching Only Pretest–Posttest Control Group Design. The subjects of the study were students of the Elementary School Teacher Training and Education Study Program, FKIP, Bengkulu University who took the Dance Arts Education course in elementary school. The findings of this study are that the learning model developed is effective in developing students' cultural literacy. This is indicated by the results of the t-test of the posttest value of the experimental class and the control class with a Sig. (2-tailed) value of 0.001, which is smaller than the significance level of 5% (0.05), so there is a significant difference between the values of the experimental class and the control class.